2015
DOI: 10.1007/s10661-015-4602-7
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic resin pellets on an urban tropical beach in Colombia

Abstract: Microplastics are a problem in oceans worldwide. The current situation in Latin America is not well known. This paper reports, for the first time, the presence of microplastics on an urban Caribbean beach in Cartagena, Colombia. Pellet samples were collected from a tourist beach over a 5-month period covering both dry and rainy seasons. Pellets were classified by color and their surface analyzed by stereomicroscopy, and some were characterized by infrared spectroscopy. The most abundant pellets were white, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(33 citation statements)
references
References 49 publications
0
22
1
2
Order By: Relevance
“…From abandoned gillnets hundreds of meters in length to plankton sized fragments, synthetic polymers have been extracted from remote corners of the Earth’s biosphere. Plastics have been quantified in marine environments [ 3 ] that include segments of the pelagic biome [ 4 ] coastal habitats [ 5 ], deep sea sediments [ 6 , 7 ], as well as freshwater lakes [ 8 , 9 ] and associated tributaries [ 10 ]. Particles have also turned up in Arctic sea ice [ 11 ], ambient air [ 12 ], and a plethora of biota such as seabirds [ 13 , 14 ], aquatic mammals [ 15 ], fish [ 16 ], and benthic invertebrates [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…From abandoned gillnets hundreds of meters in length to plankton sized fragments, synthetic polymers have been extracted from remote corners of the Earth’s biosphere. Plastics have been quantified in marine environments [ 3 ] that include segments of the pelagic biome [ 4 ] coastal habitats [ 5 ], deep sea sediments [ 6 , 7 ], as well as freshwater lakes [ 8 , 9 ] and associated tributaries [ 10 ]. Particles have also turned up in Arctic sea ice [ 11 ], ambient air [ 12 ], and a plethora of biota such as seabirds [ 13 , 14 ], aquatic mammals [ 15 ], fish [ 16 ], and benthic invertebrates [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have investigated microplastics on Caribbean beaches (Ivar Do Sul and Costa, 2007;Monteiro et al, 2018). A study on Columbian beaches, found limited plastics (an average of 3 particles/m) (Acosta-Coley and Olivero-Verbel, 2015). Three earlier studies, focusing on plastic fragments and pellets, found relatively high levels, but in these studies no size definition is provided on the fragments identified (Debrot et al, 1999;Gregory, 1983;Wilber, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…(For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article. )(Acosta-Coley and Olivero-Verbel, 2015).…”
mentioning
confidence: 99%